"Here and Now" Therapeutic Relation in Gestalt Therapy - Vásquez Palomino, Francisco (2000)
The author considers that "any therapy can only be carried out in the now"; another focus constitutes an interference. The importance of this therapeutic relationship constitutes the primordial element in the Gestalt Therapy. All this means to be in "contact with", to be with the own "self ", with the own body, with the own breathing, with corporal attitudes and even with muscular contractions. According to the oriental philosophy this is called centration and a mental posture consistent in being alert of oneself, allowing the organism to go, without pushing or braking.